HUBUNGAN USIA DENGAN TINGKAT DEMENSIA PADA LANSIA MENURUT PEMERIKSAAAN PORTABLE STATUS MENTAL EXAMINATION DI DESA KEMANTREN KECAMATAN TULANGAN KABUPATEN SIDOARJO - Basuki, Duwi; Nur So’emah, Eka (JURNAL KEPERAWATAN SEHAT, 2015)
Dementia is a syndrome-syndrome what it is chronic or progressive decline in cognitive function where there is (i.e. the ability to process thoughts) beyond what can be expected from normal aging. This affects memory, thinking, orientation, comprehension, calculation, capacity for learning, language assessment, and consciousness are not affected. The purpose of this research was the relation of age to incidence of dementia based on PPSME on the elderly. The design study was analytic with cross sectional approach korelasional. Samples were taken with the cluster random sampling technique as much as 56 respondents. Data was collected by questionnaire PPSME instrument, and then processed in coding, editing, scoring, and tabulating and then tested with test spearman rho. of the 26 respondents were classified as mild dementia contained 15 respondents aged 55-62 years old and 11 year-old 63,75 respondents, while 10 of the respondents who were currently. There were 7 respondents aged 55 to 62 years of age and 3 respondents aged 63 – 75 years. Spearman rho was obtained test results data of α = 0.05 ρ = 0,017 then ρ < α so H0 was rejected then and H1 was accepted so that there was a relationship of age with incidence of dementia. This shows that the older the age someone thus respondents will do experience dementia in heavy categories. So expect for health care personnel to better enable health cadres to participate in the activities of posyandu elderly, so as to provide good service on the elderly.Key Words : Demensia, Elderly, PPSME, Age